Genetic Improvement of Root Growth Contributes to Efficient Phosphorus Acquisition in maize (Zea mays L.) - Yi-kai ZHANG; Fan-jun CHEN; Xiao-chao CHEN; Li-zhi LONG; Kun GAO; Li-xing YUAN; Fu-suo ZHANG; Guo-hua MI (Journal of Integrative Agriculture, 2013)
Maize plants adapt to low phosphorus (P) stress by increasing root growth. It is of importance to know the extent to which genetic improvement of root growth can enhance P acquisiton. In the present study, the contribution of root growth improvement to efficient P acquisition was evaluated in two soils using T149 and T222, a pair of near isogenic maize testcrosses which were derived from a backcross BC4F3 population. T149 and T222 showed no difference in shoot biomass and leaf area under normal growth conditions, but differed greatly in root growth. T149 had longer lateral roots and a larger root surface area compared to T222. In calcareous soil, when P was insufficient, i.e., when P was either supplied as KH2PO4 at a concentration of 50 mg P kg−1 soil, or in the form of Phy-P, Ca3-P or Ca10-P, a 43% increase in root length in T149 compared to T222 resulted in an increase in P uptake by 53%, and shoot biomass by 48%. In acid soil, however, when P supply was insufficient, i.e., when P was supplied as KH2PO4 at a concentration of 100 mg P kg−1 soil, or in the form of Phy-P, Fe-P or Al-P, a 32% increase in root length in T149 compared to T222 resulted in an increase in P uptake by only 12%, and shoot biomass by 7%. No significant differences in the exudation of organic acids and APase activity were found between the two genotypes. It is concluded that genetic improvement of root growth can efficiently increase P acquisition in calcareous soils. In acid soils, however, improvements in the physiological traits of roots, in addition to their size, seem to be required for efficient P acquisition.